A-Kinase Anchor Protein 1 deficiency causes mitochondrial dysfunction in mouse model of hyperoxia induced acute lung injury - Soundararajan, Ramani; Hernández-Cuervo, Helena; Stearns, Timothy M; Griswold, Anthony J; Patil, Sahebgowda Sidramagowda; Fukumoto, Jutaro; Narala, Venkata Ramireddy; Galam, Lakshmi; Lockey, Richard; Kolliputi, Narasaiah (Frontiers in Pharmacology, 2022)
Background: Critically ill patients on supplemental oxygen therapy eventually develop acute lung injury (ALI). Reactive oxygen species (ROS) produced during ALI perturbs the mitochondrial dynamics resulting in cellular damage. Genetic deletion of the mitochondrial A-kinase anchoring protein 1 (Akap1) in mice resulted in mitochondrial damage, Endoplasmic reticulum (ER) stress, increased expression of mitophagy proteins and pro-inflammatory cytokines, exacerbating hyperoxia-induced Acute Lung Injury (HALI). Objective: Despite a strong causal link between mitochondrial dysfunction and HALI, the mechanisms governing the disease progression at the transcriptome level is unknown. Methods: In this study, RNA sequencing (RNA-seq) analysis was carried out using the lungs of Akap1 knockout (Akap1−/−) mice exposed to normoxia or 48 h of hyperoxia followed by quantitative real time PCR and Ingenuity pathway analysis (IPA). Western blot analysis assessed mitochondrial dysfunction, OXPHOS complex (I-V), apoptosis and antioxidant proteins. Mitochondrial enzymatic assays was used to measure the aconitase, fumarase, citrate synthase activities in isolated mitochondria from Akap1−/− vs. Wt mice exposed to hyperoxia. Results: Transcriptome analysis of Akap1−/− exposed to hyperoxia reveals increases in transcripts encoding electron transport chain (ETC) and tricarboxylic acid cycle (TCA) proteins. Ingenuity pathway analysis (IPA) shows enrichment of mitochondrial dysfunction and oxidative phosphorylation in Akap1−/− mice. Loss of AKAP1, coupled with oxidant injury, significantly decreases the activities of TCA enzymes. Mechanistically, a significant loss of dynamin-related protein 1 (Drp1) phosphorylation at the protein kinase A (PKA) site Serine 637 (Ser637), decreases in Akt phosphorylation at Serine 437 (Ser47) and increase in the expression of pro-apoptotic protein Bax indicate mitochondrial dysfunction. Heme oxygenase-1 (HO-1) levels significantly increased in CD68 positive alveolar macrophages in Akap1−/− lungs, suggesting a strong antioxidant response to hyperoxia. Conclusion: Overall these results suggest that AKAP1 overexpression and modulation of Drp1 phosphorylation at Ser637 is an important therapeutic strategy for acute lung injury.